فاعلية استخدام الصور المتسلسلة في تدريس مهارة الكلام بالتطبيق على معهد عبدالرحمن بن عوف بالجامعة المحمّديّة بمالانج - Muhammad Kamil Rama (LISANIYAT, 2010)
Speaking is one of the most important abilities to study a language for children and adults as well. Speaking represents a barometer of success in teaching language. In other words, the success of language instruction is reflected in the ability of student to speak the language fluently. Therefore, instruction should be given to foster speaking ability, especially to those who are still in an early stage of studying the language.The aim of this article is to collect, analyze, and evaluate the problems, and seek the solutions to the problems. Using a classroom action research method, the writer performs several cycles of researches to solve the problems and reach an intended goal. Every cycle consists of four main steps, i.e. planning, implementation, observation, and reflection.The result of the research indicates that applying media proves effective in improving speaking skill of students of the first level. The research reveals that, 1) applying sequence picture media proves effective in improving students’ skill of pronouncing words; 2) applying sequence picture media proves effective in improving students’ understanding of speaking Arabic; 3) applying sequence picture media proves effective in improving students’ fluency of speaking Arabic; 4) applying sequence picture media proves effective in improving students’ understanding of Arabic grammar; 5) applying sequence picture media proves effective in improving students’ ability of making sentences; and 6) applying sequence picture media proves effective in improving students’ confidence of speaking Arabic.